# Do Now (3x + y) – (2x + y) 4(2x + 3y) – (8x – y)

## Presentation on theme: "Do Now (3x + y) – (2x + y) 4(2x + 3y) – (8x – y)"— Presentation transcript:

Do Now (3x + y) – (2x + y) 4(2x + 3y) – (8x – y)
Simplify each expression: (3x + y) – (2x + y) 4(2x + 3y) – (8x – y) 3(x + 4y) + 2(2x – 6y) (8x – 4y) + (-8x + 5y)

7-3, 7-4 Solving Linear Systems by Elimination
Objective: solve a system of linear equations in two variables by the Elimination method.

What is Elimination? Elimination : Eliminating one variable from a system of equations by (1) multiplying one or both equations by a constant, if necessary, and (2) adding the resulting equations.

Solving Systems by using Elimination
Multiply, if necessary, one or both equations by a constant so that the coefficients of one of the variables differ only in sign. Add the revised equations from Step 1. Combining like terms will eliminate one variable. Solve for the remaining variable. Substitute the value obtained in Step 2 into either of the original equations and solve for the other variable. Check the solution in each of the original equations.

Solve x + y = -1 x – y = 9

Solve x + 2y = -11 3x - 2y = -1

Multiply One Equation 2x – 3y = 6 4x – 5y = 8

Multiply One Equation 7x – 12y = x + 8y = 14

No Solution -4x + 8y = -12 2x – 4y = 7

Download ppt "Do Now (3x + y) – (2x + y) 4(2x + 3y) – (8x – y)"

Similar presentations